POLICY DESIGN FOR PEATLAND MANAGEMENT BASED ON PUBLIC-PRIVATE PARTNERSHIP - Zulkarnaini, Zulkarnaini; Rusli, Zaili; Nasution, Mimin Sundari; Rinto, Rinto; Mayarni, Mayarni; Mashur, Dadang (Sosiohumaniora, 2024)
This research aims to develop a peatland management plan for Riau province that is based on the ideas of public-private collaboration. Data from this qualitative descriptive research were collected through a multimodal manner: interviews, in-depth literature reviews, and secondary data sources. The data analysis approach employed an interactive model that was inspired by Emerson and Nabatchi’s work on the dynamics of collaborative governance. Interviews were conducted with members of the public and commercial sectors, as well as local communities and experts. This study found that there are recurring barriers in peatland management in Riau, such as the need for more active and robust collaboration between the government and private sectors. Although the government functions within defined boundaries, the private sector often designs programs aligned with the interests of specific stakeholder groups. This situation frequently leads to incomplete projects, overlapping programs, and inadvertent strategies. The findings show there are concerns about the future adoption of sustainable methods in peatland management due to the divide between the public and private sectors. For this reason, resolving these issues is essential to protecting Riau’s peatlands and their ecological and economic significance for future generations.